Sensory acceptance of loaf bread as affected by yam flour, margarine, and oil - Lodevico, Domingo P. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2016)
Loaf bread is widely consumed, and its sensory acceptability is essential for consumers' quality assurance. Current trends in sensory techniques for cost-effective methods in food product development are the use of screening designs. This study investigated to identify the variables that affect significantly on the sensory acceptability of loaf bread processing. The design was composed of seven variables (refined sugar, fresh milk, salt, yam flour, oil, margarine, and yeast) with eight treatments using the combination of low and high levels of the variables following the Plackett-Burman 7x8 screening design pattern. Color, taste, aroma, texture and general acceptability of the loaf bread were evaluated using a 9.00 point Hedonic scale through 20 semi-trained panelists. SPSS 11.5 and Statistica 6.0 were used to analyze the data. Results revealed that lower levels of yam flour and margarine but with high levels of oil is preferred by most panelist pertaining to taste, aroma, texture, and general acceptability except the color of the loaf bread. Lowering the levels of yam flour and margarine but with high levels of oil improved the sensory attributes of the loaf bread. It is recommended that these levels of variables be used for loaf bread optimization designs.